Kur'ân Tilavetinde Lahn Olgusu -el-Mûdih fi't-Tecvîd Örneği- - Tatlısu, Muhammet Lütfü (Muş Alparslan Üniversitesi, 2021)
Kur’ân telaffuzunda mahirane bir yol tutturmak, doğru telaffuzların bilinmesi kadar yanlış telaffuzların da bilinmesini gerektirir. Lahn diye karşılık bulan hatalı okumalar, Kur’ân tilavetinde sakınılması gereken; ses, harf ve kelimede meydana gelen kusurlardır. Kur’ân okuyucularının, pratik noktasında fem-i muhsin kişilerden ders almalarının yanı sıra bu konuda kaleme alınmış eserlerden yararlanmaları da icra edecekleri tilavetin sıhhati için önem arz etmektedir. Bu meyanda çalışmamızda tecvîd ilminin bilimsel hüviyete erişmesinde ve sistematize edilmesinde behre sahibi olan Abdulvehhâb b. Muhammed el-Kurtubî’nin (461/1068) el-Mûdih fi’t-Tecvîd adlı eserin, hatalı okumalara karşı ortaya koymuş olduğu değerlendirmeleri ele alınmıştır. Çalıştığımız bu eserde, tecvîd dediğimiz olguyu zımnen de lahn kavramını, sadece naklî boyutta değil künhüne vakıf olma perspektifiyle akıl-nakil ikilisini bir potada eriterek bir sunum gerçekleştirdiği görülmektedir. Eserde lahne dair yapılması ya da yapılmaması gerekenler, arka planında yatan özel durumlarla beraber ele alınmaktadır. Böylelikle bu eser, dolaylı olarak bize tecvîdin dilin sosyal ortamından kopuk ve rivayetçi kurallar manzumesi olmayıp ilgili dil ortamının birikiminin müşahhaslaşmış, sınırları belirlenmiş ve tarifi yapılmış bir disiplin olduğu gerçeğini göstermektedir. Bu çıkarım dolaylı olarak da lahn konusunun katı kurallar bütünü olmayıp dilde var olan fakat hoş görülmeyen bir mefhum olduğu gerçeğini göstermektedir.

Making a skillful way of pronouncing the Qur'an requires knowing the wrong pronunciations as well as knowing the correct pronunciations. Incorrect readings, which correspond to Lahn, should be avoided in the recitation of the Qur'an are the defects that occur in sound, letter and word. It is important for the readers of the Qur'an to get help from competent people, whom we call “fam al-muhsin”, both in terms of practice, and to get help from the sources written on this subject, in determining the authenticity of the recitation they will perform. In this context, in our study, the evaluations of ‘Abd al-Wahh?b al-Qurtub? (d. 461/1068), who contributed to the scientific identity and systematization of the science of tajwid, against the erroneous readings of the Qur'an in his work al-Mudih fi't-Tajwid are discussed. In this work we have studied, it has been concluded that he made a presentation by addressing the phenomenon we call tajwid, implicitly, and the concept of lahn, not only in the narration/transmission (naql) dimension, but also in the dimension of the reason/mind/aql /naql relation with the perspective of understanding its essence. In addition, in the work, the situations that should or should not be done about the phenomenon of lahn are discussed together with the special situations in the background. Thus, this work indirectly shows us the fact that tajwîd is not a set of narrative rules detached from the social environment of the language, but a discipline that has been embodied, scientificly bounded and defined by the accumulation of the relevant language environment. This inference indirectly shows the fact that the subject of lahn is not a set of strict rules, but a concept that exists in the language but is not tolerated.
The Phenomenon of “Lahn” in the Recitation of Quran: the Example of al-M?d?i? f? al-Tajw?d
dinbil
Keywords: Tecvîd; Lahn; Fonetik; Ses; Med; Tajwîd; Lahn; Phonetics; Voice; Med